Cross-section of the photoeffect averaged over the atomic electrons - S. N. Fedotkin (Ядерна фізика та енергетика)
Simple approximate method for calculation of the cross sections of the photoeffect averaged over all atomic electrons is suggested. This method is based on the statistical Thomas - Fermi model with a new additional assumption. The proposed approach allows to calculate rather simply the average probabilities of various processes with participation of all atomic electrons. For this purpose averaged density of the atomic electrons is calculated analytically. Good agreement between the total cross-sections for all atomic electrons calculated in the described approach and in the framework of the quantum mechanics is obtained.